Asesmen Otentik Berbasis Ceklis dan Quizizz dalam Penilaian Perkembangan Kognitif Anak Usia Dini - Luluk Asmawati Luluk; Siti Prestia Ningsih; Dea Amalia; Anggita Septiana Dewi; Inta Innaya Putri; Nurun Nisa; Atika Ayu Rissa (Journal Ashil: Jurnal Pendidikan Anak Usia Dini, 2026)
This study aims to analyze the process and outcomes of children’s cognitive development using authentic assessments based on checklists and Quizizz. The Quizizz application serves as an innovation to support the assessment process, making it more authentic and interactive. The research method employed a naturalistic qualitative approach. The subjects consisted of 10 children aged 5–6 years at TKIT Insan Ceria in Cilegon City. Data collection techniques included participatory observation, documentation of checklist assessment results, and Quizizz. The research findings are as follows: (1) children’s cognitive development showed very good progress, (2) the authentic checklist assessment indicated very good results, (3) the use of the Quizizz app demonstrated very good outcomes. Interactive quiz-based learning enhances children’s active engagement and supports the development of logical thinking skills, memory, concentration, and the courage to make decisions. The checklist instrument helps teachers observe and record children’s developmental achievements systematically, objectively, and continuously. The conclusion is that authentic checklist assessments and the use of the Quizizz app can significantly improve the process and outcomes of cognitive development in early childhood. These findings reinforce that authentic assessment greatly assists teachers in observing and analyzing children’s developmental achievements in an authentic and contextual manner.